A Replicative Self-Renewal Model for Long-Lived Plasma Cells: Questioning Irreversible Cell Cycle Exit - Tooze, Reuben M. (Frontiers in Immunology, 2013)
Plasma cells are heterogenous in terms of their origins, secretory products and lifespan. A current paradigm is that cell cycle exit in plasma cell differentiation is irreversible, following a pattern familiar in short-lived effector populations in other haemopoietic lineages. This paradigm no doubt holds true for many plasma cells whose lifespan can be measured in days following the completion of differentiation. Whether this holds true for long-lived bone marrow plasma cells that are potentially maintained for the lifespan of the organism is less apparent. Added to this the mechanisms that establish and maintain cell cycle quiescence in plasma cells are incompletely defined. Gene expression profiling indicates that in the transition of human plasmablasts to long-lived plasma cells a range of cell cycle regulators are induced in a pattern that suggests a quiescence program with potential for cell cycle re-entry. Here a model of relative quiescence with the potential for replicative self-renewal amongst long-lived plasma cells is explored. The implications of such a mechanism would be diverse, and the argument is made here that current evidence is not sufficiently strong that the possibility should be disregarded.